Migration of Founder Epithelial Cells Drives Proper Molar Tooth Positioning and Morphogenesis - Prochazka, Jan; Prochazkova, Michaela; Du, Wen; Spoutil, Frantisek; Tureckova, Jolana; Hoch, Renee; Shimogori, Tomomi; Sedlacek, Radislav; Rubenstein, John L; Wittmann, Torsten; Klein, Ophir D (Developmental cell, 2015)
The proper positioning of organs during development is essential, yet little is known about the regulation of this process in mammals. Using murine tooth development as a model, we have found that cell migration plays a central role in positioning of the organ primordium. By combining lineage tracing, genetic cell ablation, and confocal live imaging, we identified a migratory population of Fgf8-expressing epithelial cells in the embryonic mandible. These Fgf8-expressing progenitors furnish the epithelial cells required for tooth development, and the progenitor population migrates toward a Shh-expressing region in the mandible, where the tooth placode will initiate. Inhibition of Fgf and Shh signaling disrupted the oriented migration of cells, leading to a failure of tooth development. These results demonstrate the importance of intraepithelial cell migration in proper positioning of an initiating organ.
Keywords: odontogeneze; Odontogenesis; fibroblastové růstové faktory; mezoderm; epitelové buňky; zvířata; myši; Mice; Morphogenesis; Mesoderm; Gene Expression Regulation, Developmental; morfogeneze; Epithelial Cells; pohyb buněk; Cell Movement; moláry; Fibroblast Growth Factors; Tooth; vývojová regulace genové exprese; Animals; zuby; Molar